Using Peer Crowds to Segment Black Youth for Smoking Intervention. Issue 4 (July 2014) - Lee, Youn Ok; Jordan, Jeffery W.; Djakaria, Mayo; Ling, Pamela M.
Studies of peer crowds show promise for enhancing public health promotion and practice through targeting. Distinct images, role models, and social norms likely influence health behaviors of different peer crowds within health disparity groups. We describe peer crowds identified by Black young people and determine whether identification with them is associated with smoking. Data from Black young people aged 13 to 20 years in Richmond, Virginia, were collected via interview and online survey ( N = 583). We identified the number and type of peer crowds using principal components analysis; associations with smoking were analyzed using Pearson chi-square tests and logistic regression. Three peer crowds were identified—"preppy, " "mainstream, " and "hip hop." Youth who identify with the hip hop peer crowd were more likely to smoke and have friends who smoke and less likely to hold antitobacco attitudes than those identifying with preppy or mainstream crowds. Identifying with the hip hop crowd significantly increased the odds of smoking, controlling for demographic factors (odds ratio = 1.97; 95% confidence interval = 1.03-3.76). Tobacco prevention efforts for Black youth and young adults should prioritize the hip hop crowd. Crowd identity measures can aid in targeting public health campaigns to effectively engage those at highest risk.